2020
DOI: 10.1371/journal.pone.0229060
|View full text |Cite
|
Sign up to set email alerts
|

Differential virulence of Trypanosoma brucei rhodesiense isolates does not influence the outcome of treatment with anti-trypanosomal drugs in the mouse model

Abstract: We assessed the virulence and anti-trypanosomal drug sensitivity patterns of Trypanosoma brucei rhodesiense (Tbr) isolates in the Kenya Agricultural and Livestock Research Organization-Biotechnology Research Institute (KALRO-BioRI) cryobank. Specifically, the study focused on Tbr clones originally isolated from the western Kenya/eastern Uganda focus of human African Trypanosomiasis (HAT). Twelve (12) Tbr clones were assessed for virulence using groups(n = 10) of Swiss White Mice monitored for 60 days post infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…These results confirmed the existence of differential virulence among the isolates. Differential virulence and pathogenicity of trypanosomes has previously also been reported for other samples of Tyrpanosoma brucei rhodesiense isolates in mice, 28 Trypanosoma brucei rhodesiense isolates in vervet monkeys 29 ; Trypanosoma brucei brucei and Trypanosoma congolense strains in mice 25,31-33 and T. evansi isolates in mice. 34 In the present work, we have additionally shown that mice groups infected with CNS derived trypanosomes also exhibited differential virulence, indicating that this attribute is independent of the environment from which the trypanosomes are recovered.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These results confirmed the existence of differential virulence among the isolates. Differential virulence and pathogenicity of trypanosomes has previously also been reported for other samples of Tyrpanosoma brucei rhodesiense isolates in mice, 28 Trypanosoma brucei rhodesiense isolates in vervet monkeys 29 ; Trypanosoma brucei brucei and Trypanosoma congolense strains in mice 25,31-33 and T. evansi isolates in mice. 34 In the present work, we have additionally shown that mice groups infected with CNS derived trypanosomes also exhibited differential virulence, indicating that this attribute is independent of the environment from which the trypanosomes are recovered.…”
Section: Discussionsupporting
confidence: 63%
“…High trypanosome numbers are frequently, but not always, associated with increased pathogenicity. 28,39 We monitored the development of anaemia which is one of the major trypanosome-induced pathologies and is a possible biomarker of parasite pathogenicity and virulence. The main characteristic of the murine trypanosome-induced anaemia was the rapidity of its onset in all the infected mice as shown by PCV declines by an average of 30% by 14 days post infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the multiple drug resistance observed in this study is at the population level and most likely not at the individual trypanosome level where treatment using a “sanative pair” would have been impossible [ 42 ]. Ndungu et al [ 30 ] demonstrated that several clones derived from an isolate that exhibited resistance to trypanocidal drugs in mice showed variable sensitivity to treatment. Whether the clones from the multiple resistant isolates from this study could have variable sensitivity to diminazene, homidium and isometamidium was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that resistant trypanosome populations vary greatly in the sensitivity of individual trypanosomes in that population [ 27 29 ]. In addition, Ndung’u et al [ 30 ] demonstrated the existence of variations in virulence and sensitivity of T . b .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation